(untitled) (Novateur Publications, 2023)
Indonesia as a constitutional state has provided sufficient space for the implementation of religion for the benefit of all citizens. Specifically regarding freedom of religion and/or belief, the constitution has also provided very broad guarantees. Therefore, everyone is free to embrace religion and worship according to their religion. In fact, everyone has the right to freedom of belief. Of course, including expressing thoughts and attitudes, according to his conscience. This research takes the subject of freedom of religion and belief in the rule of law. The purpose of the research is to find out that the rights and freedoms of religion or belief are free choices according to one’s conscience, so they must be respected. There is no institution whatsoever that can impede, negate or impose religion. This research is an empirical research that uses a sociological juridical approach. The reality of conditions that exist in the regions, in the research conducted found various advances, there is understanding/awareness of citizens of the rights and obligations in carrying out religious worship in the Indonesian legal state. That is the progress of our constitution in regulating religious freedom issues in this republic.a